(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Manipol MM, Tinio CE, Maldia LSJ, Combalicer MS. 2020. Salinity-induced changes in the morphology, physiology, and anatomy of seeds and seedlings of smooth narra (Pterocarpus indicus Willd. f. indicus). Biodiversitas 21: 5146-5154. Pterocarpus indicus Willd. forma indicus is a commonly planted species for reforestation in the Philippines regardless of the area’s condition. Since the species could survive in areas even with harsh conditions, it was hypothesized that the species may also thrive in areas having substantial amount of salt, especially during its early growth. This study assessed the morphological, physiological, and anatomical responses of seeds and seedlings of P. indicus Willd. f. indicus (Fabaceae), a native species in the Philippines to varying salt (NaCl) concentrations (0-300 mM). Based on the results, P. indicus f. indicus grew significantly in terms of height, number of leaves, leaf area, root collar diameter (RCD), root nodules, and root-shoot ratio in the control and at 100 mM NaCl. On the other hand, the growth of the species was suppressed at 300 mM NaCl. The physiological characteristics (germination, survival, and photosynthetic rates) were also high in the control compared to the NaCl treatments. As for the seed anatomical characteristics, the radicle cells remained undamaged, with high cell number and longer cells in the control, but showed damaged and reduced cell number and length at 300 mM NaCl. This indicates that P. indicus f. indicus can only tolerate moderate saline soil conditions. Hence, this result needs to be considered in reforestation efforts of the country using this species.